IMPLEMENTATION REVENUE RECOGNITION OF PSAK 34 IN CONSTRUCTION COMPANIES - Simon, Febryanti; Hartsetyo, Angelia Putri; Sudrajat, Kansa Dwi Putri Angelina (LPPM Universitas Bina Bangsa, 2025)
This study aims to determine the construction contract revenue recognition method used in heavy construction & civil engineering sub-sector companies and its application in accordance with PSAK No. 34. The research method used is descriptive qualitative method (deep analysis) with purposive sampling data collection technique. The results of this study indicate that in general, heavy construction & civil engineering sub-sector companies listed on the IDX have made revenue disclosures in accordance with PSAK No. 34, except for several companies that still have not disclosed their construction contract revenue recognition methods